Analysis of drift correction in different simulated weighing schemes. (September 2015) - Beatrici, A; Rebelo, A; Quintão, D; Cacais, F L; Loayza, V M
Abstract: In the calibration of high accuracy mass standards some weighing schemes are used to reduce or eliminate the zero drift effects in mass comparators. There are different sources for the drift and different methods for its treatment. By using numerical methods, drift functions were simulated and a random term was included in each function. The comparison between the results obtained from ABABAB and ABBA weighing series was carried out. The results show a better efficacy of ABABAB method for drift with smooth variation and small randomness.